Enhanced Field-Oriented Control for Synchronous Reluctance Motor Using Fuzzy Logic - Madbouly, Sayed O. (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
This paper presents a fuzzy logic-based Field Oriented Control (FOC) strategy for synchronous reluctance motors (SynRMs). The proposed algorithm addresses the inherent nonlinearities and parameter sensitivities of SynRMs by integrating fuzzy logic control (FLC) into the FOC framework, enhancing system robustness and adaptability. The SynRM model is derived in the rotor reference frame, with two control loops implemented: one for speed control and the other for flux control. Two FLCs are utilized in the speed control loop, while one FLC is adopted in the flux control loop. Fuzzy sets, membership functions, and rule bases enable dynamic parameter tuning. The entire system is simulated in MATLAB/Simulink. The system's dynamic performance is rigorously evaluated in two scenarios: with decoupling control components between the speed and flux control loops, and without these components under various loading conditions. Comprehensive simulations demonstrate that the proposed control algorithm, without decoupling control components, exhibits superior dynamic performance in terms of rise time, overshoot, and settling time. Furthermore, eliminating the decoupling components reduces the system's dependency on machine parameters while having a minor effect on undershoot.